Direct and semi-direct aerosol effects on the southern African regional climate during the austral winter season - (:unkn) unknown (My University, 2011)
The regional climate model RegCM3 is used to investigate the direct and semi-direct aerosol effects on the southern African climate during the austral winter season (June-September). The sensitivity of simulated aerosol-climate effects to different biomass burning inventories, boundary conditions and sea surface temperature (SST) feedbacks is tested to assess the range of uncertainty associated with these parameters. Little sensitivity to boundary forcing is found, while the aerosol radiative forcing (RF) varies approximately linearly by up to a factor of two, in response to the factor of two difference between emissions inventories. In all cases the surface RF is negative, while the top-to-atmosphere RF is negative over most of the domain but positive over high-albedo savannah regions where aerosol loading is high. Sensitivity to SST feedbacks is negligible in RegCM3. Although the magnitude of simulated RF varies, all simulations show similar aerosol-climate impacts. Surface temperature decreases over most of the subcontinent, a signal which acts to reduce model bias over the western half of the region. The absorbing nature of the simulated aerosol burden results in heating at altitude, which, in combination with the surface cooling, serves to increase stability in the lower atmosphere over most of the subcontinent. In the middle troposphere, however, this warming induces an elevated heat-pump effect in the equatorial regions between approximately 8°N and 5°S. This enhances convection, precipitation as well as soil moisture, effectively spinning-up the hydrological cycle in the tropics. An investigation of the interannual variability of the simulated aerosol radiative impacts showed that seasonal average precipitation changes varied more from year to year than aerosol-induced surface temperature changes. In contrast, despite significant differences between synoptic conditions, there is little synoptic-scale variability of aerosol-climate impacts. Th
Keywords: African Research